PERPUSTAKAAN ERA ISLAM KLASIK DAN PERKEMBANGANNYA DI LEMBAGA PENDIDIKAN ISLAM INDONESIA SAAT INI - Afrizal Afrizal (UIN Imam Bonjol Padang, 2017)
This paper discusses the glory of Islamic civilization in the past through the development of science. Besides that, it also discussed about the condition of the library in Islamic educational institutions in general, which was so concerned and seemed not to get the attention of various parties concerned. In fact, the library is a window of science and information because that is where the user will be able to discover new things